E-Learning On Three Phase Induction Motor - Mohd Hasanizal , Kamaruzaman (UTeM, 2009)
This project is a software base which contains a learning course on three phase induction motor. As we know that three phase induction motors are widely used in industrial and commercial applications. But students have are facing problems for understanding about the basic of three phase induction motor because they cannot see physical phenomena inside the induction motor such as squirrel cage rotor and wound rotor of induction motor. This courseware contains the characteristic of three phase induction motor. This courseware will provide a wonderful experience with the matter being studied and the users can't understand three phase induction motor easily. This courseware also uses the Macromedia Flash 8 software in order to design and create the slide, animation, illustration and some examples related to this subject. So, by following the methodology and some steps in this software, the result will be successfully and the objectives in this project is achieved.